The influence of movement on the occupancy–density relationship at small spatial scales. Issue 8 (1st August 2019) - Rogan, Matthew S.; Balme, Guy A.; Distiller, Greg; Pitman, Ross T.; Broadfield, Joleen; Mann, Gareth K. H.; Whittington‐Jones, Gareth M.; Thomas, Lisa H.; O'Riain, M. Justin
Abstract: The global decline of large carnivores demands effective and efficient methods to monitor population status, particularly using non‐invasive methods. Density is among the most useful metrics of population status because it is directly comparable across space and time. Unfortunately, density is difficult to measure reliably, especially for mobile, cryptic species. Recently, efforts have turned to approximating density based on its relationship to more readily estimable indices of occurrence. However, the relationship between density and such indices is contingent on several key assumptions that field studies often violate. Recent research has shown that these relationships are unreliable where sampling units are not independent, as is often the case when estimating density or occurrence of large carnivores. Here, we use the largest data set thus far collected for leopards ( Panthera pardus ) — 88 camera‐trap surveys undertaken in 24 protected areas between 2013 and 2018—to explore how density and other population characteristics relate to parameter estimates in occupancy and Royle–Nichols abundance models. We show how home‐range size confounds underlying relationships, with larger home ranges inflating the proportion of area used (PAU) and resulting in double counting in abundance models. Relativizing estimates of occupancy and abundance by home‐range size improved their relationship with density, but the relationship remained weak and largely uninformative for management. Our findings illustrate the pitfalls of using the PAU or abundance as implicit proxies for density and highlight the challenges of assessing population status for wide‐ranging, cryptic species across fragmented landscapes.